Uridine diphosphate (UDP)-glycosyltransferases (UGTs) are associated with insecticide resistance in the major malaria vectors Anopheles gambiae s.l. and Anopheles funestus - Logan, Rhiannon; Mäurer, Julia; Wapler, Charlotte; Ingham, Victoria (Scientific reports, 2024)
Malaria remains one of the highest causes of morbidity and mortality, with 249 million cases and over 608,000 deaths in 2022. Insecticides, which target the Anopheles mosquito vector, are the primary method to control malaria. The widespread nature of resistance to the most important insecticide class, the pyrethroids, threatens the control of this disease. To reverse the stall in malaria control there is urgent need for new vector control tools, which necessitates understanding the molecular basis of pyrethroid resistance. In this study we utilised multi-omics data to identify uridine-diphosphate (UDP)-glycosyltransferases (UGTs) potentially involved in resistance across multiple Anopheles species. Phylogenetic analysis identifies sequence similarities between Anopheline UGTs and those involved in agricultural pesticide resistance to pyrethroids, pyrroles and spinosyns. Expression of five UGTs was characterised in An. gambiae and An. coluzzii to determine constitutive over-expression, induction, and tissue specificity. Furthermore, a UGT inhibitor, sulfinpyrazone, restored susceptibility to pyrethroids and DDT in An. gambiae, An. coluzzii, An. arabiensis and An. funestus, the major African malaria vectors. Taken together, this study provides clear association of UGTs with pyrethroid resistance as well as highlighting the potential use of sulfinpyrazone as a novel synergist for vector control.